SLOPE STABILITY ANALYSIS OF P3 WEST GRASBERG MINE PT FREEPORT INDONESIA USING THE ROCK MASS CLASSIFICATION METHOD - ENRICO SITOHANG (NIM 12103056), ROY
Presumption of the existence of the local geological structures such as fold around the P3 West slope have triggered more detail research about the effect of the cracks existence and orientation to the slope stability condition. Core Orienting activity had done to collect the information about the existence, orientation and characteristic of the cracks. Results of this Core Orienting activity were analyzed using the rock mass classification methods such as Rock Mass Rating (RMR) and Slope Mass Rating (SMR) to gather information about the slope stability condition. Generally, the results of this research show that the rock mass RMR values are classified into fair rock mass class (RMR range 41-60) and good rock mass class (RMR range 61-80). Also the rock mass SMR values are classified into good rock mass class (SMR range 61-80) and very good rock mass class (SMR range 81-100). It indicates that generally, the P3 West slope is in a stable condition and the probability of the failure that might happen is just in some small blocks. So, there is no need using the supporting system for this slope. The SMR rock mass classification method has a limitation in slope stability analysis because it doesn't calculate the influence of slope geometry to the slope stability condition. It should not be used as the only way to analyze and design a slope. Therefore, some further research using the slope modeling is needed.